Réponses

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-05-05T01:18:34+02:00
Salut,
1.
2x - 3 ≥ x + 1
2x - x ≥ 3 + 1
x ≥ 4

2

a. L'aire du rectangle BCEF est ABCD - AFED.
ABCD = (2x-3)² et AFED = (2x-3)(x+1)

A = (2x-3)² - (2x-3)(x+1)

b.
A = (2x-3)² - (2x-3)(x+1)
A = (4x² - 12x + 9) - (2x² + 2x - 3x - 3)
A = (4x² - 12x + 9) - (2x² - x - 3)
A = 4x² - 12x + 9 - 2x² + x + 3
A = 2x² - 11x + 12

c.
A = (2x-3)² - (2x-3)(x+1)
A = (2x-3)[(2x-3) - (x+1)]
A = (2x-3)(2x - 3 - x - 1)
A = (2x-3)(x-4)

d.

(2x-3)(x-4) = 0
2x - 3 = 0
2x = 3
x = 3/2
x - 4 = 0
x = 4.

e.
L'aire du rectangle est nulle quand x = 4 ou x = 3/2.

Bonne soirée !